Study of 3D and 4D password Security - Khurana, Smriti; Patel, Mili; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
3d & 4d passwords which are more famous and very interesting way of security, the human memory in our scheme has to undergo the facts of verified. these passwords are used to secure data or user accounts, these passwords famous technique is based on a combination of multiple set of facts the international company develops and distributes the 4th dimension server s/w 4d owns located in the USA Germany JAPAN & Australia these passwords is the most commonly used recall based authentication scheme used in the computer world where security is needed passwords has one major disadvantage due to its two contradictory requirements at the same time password selection must be easy to remember and tough to guess 4d passwords as a oneup method to the 3d password the 3d password scheme is a relatively new authentication scheme that combines recognition + recall + tokens +biometric in on authentication system